Partial Cutting of Sternothyroid Muscle during Total Thyroidectomy: Impact on Postoperative Vocal Outcomes - Hyoung Shin Lee; Sung Won Kim; Hyo Sang Park; Chan Woo Park; Ji Soo Kim; Jong Chul Hong; Yong-Ki Kim; Seon Mi Baek; Kang Dae Lee (The Scientific World Journal)
Background. Cutting the sternothyroid (ST) muscle is a useful technique to expose the superior pole of thyroid gland during thyroidectomy. In this study, we evaluated the impact of partial cutting of the ST muscle on postoperative vocal outcomes after total thyroidectomy. Methods. A retrospective review of 57 patients who underwent total thyroidectomy with central neck dissection for micropapillary thyroid carcinoma was conducted. Group A (n=26) included those without cutting the ST muscle, while group B (n=31) included patients whose muscle was partially cut at the superior pole. All patients underwent voice analysis before the operation and 2 weeks and 1 month after the surgery, and the outcomes were compared between the two groups. Results. There were no differences between the two groups regarding the outcomes at each time of voice analysis. Group A showed a decrease of maximum frequency 2 weeks after surgery but showed no difference after 1 month. Group B showed a mild decrease in maximum frequency 2 weeks after surgery, but the difference was not significant. Conclusion. Partial cutting of ST muscle during thyroidectomy is useful to expose the superior pole without significant negative impact on postoperative outcomes of vocal analysis.